The heiress : the revelations of Anne de Bourgh - Greeley, Molly (William Morrow, an imprint of HarperCollinsPublishers, 2021)
"As a fussy baby, Anne was prescribed laudanum to quiet her and has been given the opium-heavy syrup ever since, on account of her continuing ill health. While Lady Catherine is outraged when Darcy chooses not to marry her daughter, Anne barely even notices. But little by little, she comes to see that what she has always been told is an affliction of nature might in fact be one of nurture - and one, therefore, that she can beat. She finally throws away her laudanum and seeks refuge at the London home of her cousin, Colonel Fitzwilliam. Suddenly wide awake to the world but utterly unprepared, Anne must forge a new identity among those who have never seen the real her - including herself."--Publisher.